Ethical Aspects of Sustainable Development in Polish Enterprises Transporting Animals for Slaughter - Budzik, Anna; Budzik, Tomasz (European Journal of Sustainable Development, 2019)
The issue of sustainable development is currently the subject of interest of researchers from many scientific fields. The idea of sustainable development includes the economy, the society and the environment. In the context of sustainable development, the subject of animal welfare is being increasingly regarded as essential. Ensuring animal welfare is now the key issue for public opinion, livestock farmers, animal rights organizations, entrepreneurs, transport companies and slaughterhouses. Animal welfare should be applied according to Five Freedoms, which are: freedom from hunger and thirst, freedom from pain and injury, freedom from physical discomfort, freedom to express normal behavior, freedom from stress and fear. The purpose of this article is to present the current state of awareness about ensuring animal welfare as an element of sustainable development on the example of Polish companies which transport animals to slaughterhouses. As a research method the authors used the survey method. The questionnaire was addressed to the owners of enterprises transporting slaughter animals and to drivers of these enterprises. The results found out that there is a serious need to change the operation of the transport system due to ethical aspects. Keywords: Sustainable development, animal welfare, animal transport, transport management